Exceptional learners: an introduction to special education - Hallahan, Daniel; Kauffman, James (New York: Pearson, 2006)
Contents: Exceptionality and special education. Current trends and Issues. Multicultural and bilingual aspects of special educatiion. Parents and families. Learners with mental retardation. Learners with learning disabilities. Attention deficit hyperativy disorder. Learners with emoitional os behavioral disorders. Learners with communication disorders. Learners who are deaf or hard of hearing. Learners with blindness or low vision. Learners with autism sprectrum disorders. Learners with low incidence, multiple, and severe disabilities. Learners with physical disabilities. Learners with special gifs and talents
Keywords: Educación Especial